Organization of foreign specialists’ professional training in Russian higher education institutions: principal objectives - P. V. Krahotkin (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. Foreign specialists’ training in Russian higher educational institutions is one of the priority areas of cooperation, which, of course, aﬀects the state of competitiveness of Russian universities and the strengthening of the security system of Russia as a whole.Goal. The purpose of presented study is to consider the principal objectives of foreign specialists’ professional becoming in Russian higher educational establishments.Materials and methods. To achieve the subjective, general scientiﬁc methods: analysis of sources on research issues; their comparison, generalization of research results were used.Results and discussion. Foreign specialists’ professional training is aimed not only at acquiring knowledge and skills which allow them to eﬀectively implement their professional activities, perform their functional professional duties, but also at formation of person’s signiﬁcant qualities which provide constructive relationships with the partners and the social environment – taking into account the multiculturalism and multi-confessional society.Conclusion. It is quite obvious that contacts between people of diﬀerent countries, cultural exchanges are extremely important for the development of mutual understanding, friendship and cooperation between the peoples of the Russian Federation and foreign countries.